On an efficient modification of the Chebyshev method. Issue 6 (24th November 2021) - Ezquerro, José Antonio; Hernández‐Verón, Miguel Ángel; Alberto Magreñán, Ángel
Abstract: An efficient modification of the Chebyshev method is constructed from approximating the second derivative of the operator involved by combinations of the operator in different points and it is used to locate, separate, and approximate the solutions of a Chandrasekhar integral equation from analysing its global convergence.